Exosomes and diabetes. Issue 3 (7th January 2019) - Castaño, Carlos; Novials, Anna; Párrizas, Marcelina
Summary: Diabetes is a group of metabolic diseases characterized by elevated blood glucose levels that drive the development of life‐threatening complications. Diabetes results from a situation of insufficient insulin action, either by deficient production of the hormone by the pancreas, or by the development of insulin resistance in peripheral tissues such as liver, muscle, or the adipose depots. Communication between organs is thus central to the maintenance of glucose homoeostasis. Recently, several studies are evidencing that small vesicles called exosomes released by, amongst other, the adipose tissue can regulate gene expression in other tissues, hence modulating interorgan crosstalk. Therefore, exosomes participate in the development of diabetes and its associated complications. Their study holds the potential of providing us with novel biomarkers for the early diagnosis and stratification of patients at risk of developing diabetes, hence allowing the timely implementation of more personalized therapies. On the other hand, the molecular dissection of the pathways initiated by exosomes under situations of metabolic stress could help to gain a deeper knowledge of the pathophysiology of diabetes and its associated metabolic diseases.